# Chain Rule for Differentiation

We at ask-math believe that educational material should be free for everyone. Please use the content of this website for in-depth understanding of the concepts. Additionally, we have created and posted videos on our youtube.

We also offer One to One / Group Tutoring sessions / Homework help for Mathematics from Grade 4th to 12th for algebra, geometry, trigonometry, pre-calculus, and calculus for US, UK, Europe, South east Asia and UAE students.

Affiliations with Schools & Educational institutions are also welcome.

Please reach out to us on [email protected] / Whatsapp +919998367796 / Skype id: anitagovilkar.abhijit

We will be happy to post videos as per your requirements also. Do write to us.

The chain rule for differentiation deals with the composite functions.
For example compare the functions below :
 Without the chain rule 1) $x^{3}+1$ 2) cos(x) 3) (2x+1) 4) x + sin(x) With the chain rule 1) $\sqrt{x^{3}+1}$ 2) cos(4x) 3) $(2x +1)^{4}$ 4) x + $sin(x)^{2}$
Basically, the Chain Rule states that if 'y' changes dy/du times as fast as 'u' and 'u' changes du/dx times as fast as 'x' then 'y' changes (dy/du)(du/dx) times as fast as 'x'.

Theorem : (chain rule) If f(x) or u and g(x) or v are differentiable functions, then (f O g) is also differentiable and
(f O g)' = f'(g(x)). g'(x)

OR

$\frac{\text{d}}{\text{d}x} [(f O g)(x)] = \frac{\text{d}}{\text{d}g(x)}[(f O g)(x)].\frac{\text{d}}{\text{d}x}((g(x))$

$\frac{\text{d}y}{\text{d}x}= \frac{\text{d}y}{\text{d}u}.\frac{\text{d}u}{\text{d}x}$

Proof :
Since f(x) and g(x) are the differentiable functions. Therefore, according to the definition of derivative

$\frac{\text{d}}{\text{d}x} [(f(x)] =\lim_{\triangle x \rightarrow 0}\frac{f(x+\triangle x) -f(x)}{\triangle x}$

$\frac{\text{d}}{\text{d}x} [g(x)] =\lim_{\triangle x \rightarrow 0}\frac{g(x+\triangle x) -f(x)}{\triangle x}$

Now, $\frac{\text{d}}{\text{d}x} [(f O g)(x)]=\lim_{\triangle x \rightarrow 0}\frac{fOg(x+\triangle x) -fOg(x)}{\triangle x}$

$=\lim_{\triangle x \rightarrow 0}\frac{f[g(x+\triangle x)] -f[g(x)]}{\triangle x}$

$=\lim_{\triangle x \rightarrow 0}\frac{f[g(x+\triangle x)] -f[g(x)].[g(x + \triangle x) - g(x)]}{\triangle x.[g(x + \triangle x) - g(x)]}$

$=\lim_{\triangle x \rightarrow 0}\frac{f[g(x+\triangle x)] -f[g(x)]}{[g(x + \triangle x) - g(x)]}.\lim_{\triangle x \rightarrow 0}\frac{g(x + \triangle x) - g(x)}{\triangle x}$

$=\lim_{g(x+h) \rightarrow g(x)}\frac{f[g(x+\triangle x)] -f[g(x)]}{[g(x + \triangle x) - g(x)]}.\lim_{\triangle x \rightarrow 0}\frac{g(x + \triangle x) - g(x)}{\triangle x}$

(since g(x) is differentiable, g(x) is continuous and hence $\lim_{\triangle x \rightarrow 0}(x + \triangle x) = g(x))$

$\frac{\text{d}}{\text{d}x} [(f O g)(x)] = \frac{\text{d}}{\text{d}g(x)}[(f O g)(x)].\frac{\text{d}}{\text{d}x}((g(x))$

## Examples on Chain Rule for Differentiation

Example 1: Differentiate with respect to x
y= sin($x^{2} +1 )$
Solution : y= sin($x^{2} +1 )$
Let u = $x^{2} +1$
y= sin(u) and u =$x^{2} +1$
$\frac{\text{d}y}{\text{d}u}= cos(u)$ and $\frac{\text{d}u}{\text{d}x}= 2x$

Now by chain rule for differentiation,

$\frac{\text{d}y}{\text{d}x}= \frac{\text{d}y}{\text{d}u}.\frac{\text{d}u}{\text{d}x}$

$\frac{\text{d}y}{\text{d}u}= cos(u).2x$

= 2x cos($x^{2}+1)$

$\frac{\text{d}}{\text{d}x}[sin(x^{2} +1)] = 2x cos(x^{2} +1)$

Example 2: Differentiate with respect to x
y= ($e^{sin(x)} )$
Solution : y= ($e^{sin(x)} )$
Let u = sin(x)
y= $e^{u}$ and u = sin(x)
$\frac{\text{d}y}{\text{d}u}=e^{u}$ and $\frac{\text{d}u}{\text{d}x}= cos(x)$

Now by chain rule for differentiation,

$\frac{\text{d}y}{\text{d}x}= \frac{\text{d}y}{\text{d}u}.\frac{\text{d}u}{\text{d}x}$

$\frac{\text{d}y}{\text{d}u}= e^{u}.cos(x)$

= $e^{sin(x)}.cos(x)$

$\frac{\text{d}}{\text{d}x}[(e^{sin(x)} )] = e^{sin(x)}.cos(x)$